Dr. Novel missense variant L46Q of fatty acid synthase gene and fatty acids content in Awassi sheep - Tahreer Mohammed Al-Thuwaini; Zahraa Aqeel Kareem (Acta Scientiarum. Animal Sciences, 2022)
This study was conducted to investigate the association between the polymorphism of the FASN gene with fatty acid content in Awassi sheep. A total of 100 male Awassi sheep between the ages of one and two and a half years old were used in this study. Phenotypic measurement was recorded at slaughter, and from each animal, the longissimus dorsi (LD) muscle samples were taken to analyze the fatty acid profile. Genotyping, sequencing reactions, and in silico tools were performed to confirm the variants in amplified fragments. The result of genotyping revealed two genotypes (AA and AB) of the ovine FASN gene (exon 3). Novel SNP (L46Q) was discovered only within the FASN gene (AB genotype). All utilized in silico tools revealed remarkably deleterious effects for the L46Q on the mutant protein structure, function, and stability. Association analysis revealed that the AB genotype has significantly (p < 0.05) higher levels of animal length and monounsaturated fatty acids (MUFA) with lower amounts of saturated fatty acids (SFA) content than the AA genotype. In conclusion, novel SNP (L46Q) was discovered within the FASN gene (AB genotype), made the animals that has the AB genotype associated with good meat quality traits and this polymorphism may serve as markers for meat quality.